PENYULUHAN BAGI PESERTA DIDIK PENTINGNYA SEX EDUKASI DALAM MENCEGAH TERJADINYA KEKERASAN SEKSUAL DI SMP ST. MARKUS II JAKARTA TIMUR - Fransiska Novita Eleanora; Endang Hadrian; Anggreany Haryani Putri; Lenny Utama Afriyenti; Muhammad Aliframadhan; Hilmy Adya Laksana; Poetry Rofifah (Jurnal Pengabdian Kepada Masyarakat, 2023)
Sexual violence is an act or conduct that is considered to violate and demean and humiliate and without the consent of one party, and as a result the impact results in psychological and/or physical suffering and can interfere with a person's reproductive health. It is very important to provide understanding and education regarding learning about sex education to students and female students, where the objectives obtained from sex education are to teach and tell what can be done and what cannot be done and can also increase alertness and caution. For children about the function of the body parts. With this legal counseling, preventive efforts, namely prevention through sex education, can provide benefits for students to be able to protect themselves and avoid sexual violence.Keywords: sex education, sexual violence, prevention